2024
DOI: 10.3389/fvets.2024.1387076
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with behavioral euthanasia in pet dogs

Miranda Hitchcock,
Miranda K. Workman,
Adeline P. Guthrie
et al.

Abstract: When pet dogs demonstrate certain serious problem behaviors, this may lead owners to choose behavioral euthanasia. However, research on behavioral euthanasia of pet dogs is sparse and previously published papers have not specifically sampled owners who made the decision to euthanize for behavior. The Behavioral Euthanasia in Pet Dogs Questionnaire was created to collect a wide range of information from dog owners who made behavioral euthanasia decisions. Using this survey, we explored the types of behaviors as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 65 publications
0
0
0
Order By: Relevance
“…Similarly, an Australian-based study revealed that 29.7% of dogs under primary care that died at three years of age or under had deaths attributed to at least one problematic behaviour 55 . Many studies suggest aggression, in particular, is commonly related to premature death in younger dogs and is frequently reported as the most common cause of behavioural euthanasia [54][55][56] . As well as euthanasia, problematic behaviour has previously been discussed as a leading cause of relinquishment of young dogs to shelters 57 , as well as a factor in unsuccessful adoptions from shelters 58 .…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, an Australian-based study revealed that 29.7% of dogs under primary care that died at three years of age or under had deaths attributed to at least one problematic behaviour 55 . Many studies suggest aggression, in particular, is commonly related to premature death in younger dogs and is frequently reported as the most common cause of behavioural euthanasia [54][55][56] . As well as euthanasia, problematic behaviour has previously been discussed as a leading cause of relinquishment of young dogs to shelters 57 , as well as a factor in unsuccessful adoptions from shelters 58 .…”
Section: Discussionmentioning
confidence: 99%